Male fetal loss in the U.S. following the terrorist attacks of September 11, 2001 - Catalano Ralph; Bruckner Tim A; Ahern Jennifer (BMC, 2010)
Abstract Background The secondary sex ratio (i.e., the odds of a male birth) reportedly declines following natural disasters, pollution events, and economic collapse. It remains unclear whether this decline results from an excess of male fetal loss or reduced male conceptions. The literature also does not converge as to whether the terrorist attacks of September 11, 2001 induced "communal bereavement", or the widespread feeling of distress among persons who never met those directly involved in the attacks. We test the communal bereavement hypothesis among gravid women by examining whether male fetal deaths rose above expected levels in the US following September 11, 2001. Methods We apply interrupted time-series methods to all fetal deaths at or greater than the 20th week of gestation in the US from 1996 to 2002. Time-series methods control for trends, seasonality, and other forms of autocorrelation that could induce spurious associations. Results Results support the hypothesis in that the fetal death sex ratio (i.e., the odds of a male fetal death) increased above its expected value in September 2001. Additional analysis of the secondary sex ratio indirectly supports that the terrorist attacks may have threatened the gestation of male more than female fetuses. Conclusions Societal responses to events such as September 11, 2001 do not appear confined only to persons who have ever met the deceased. The fetal death sex ratio in the US population may serve as a sentinel indicator of the degree to which pregnant women react to population stressors.